2006
DOI: 10.1051/0004-6361:20054054
|View full text |Cite
|
Sign up to set email alerts
|

B and I-band optical micro-variability observations of the BL Lac objects S5 2007+777 and 3C 371

Abstract: We have observed S5 2007+777 and 3C 371 in the B and I bands for 13 and 8 nights, respectively, during various observing runs in 2001, 2002 and 2004. The observations resulted in almost evenly sampled light curves, 6−9 h long. We do not detect any flares within the observed light curves, but we do observe small amplitude, significant variations, in both bands, on time scales of hours and days. The average variability amplitude on time scales of minutes/hours is ∼2.5% and ∼1−1.5% in the case of S5 2007+777 and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Dai et al (2013) found an anticlockwise loop in intra-day color behavior of S5 0716+714. Xilouris et al (2006) have reported the similar pattern in optical band. In other regime like gamma-ray and X-ray, the loop path has been reported frequently (e.g.…”
Section: Color Behavior and Spectral Hysteresissupporting
confidence: 65%
“…Dai et al (2013) found an anticlockwise loop in intra-day color behavior of S5 0716+714. Xilouris et al (2006) have reported the similar pattern in optical band. In other regime like gamma-ray and X-ray, the loop path has been reported frequently (e.g.…”
Section: Color Behavior and Spectral Hysteresissupporting
confidence: 65%
“…Our main aim is to study the intra-night flux and energy spectral variations over a period of 3 nights in 2001. The quality of the light curves is similar to those presented by Xilouris et al (2006) in the case of S5 2007+777 and 3C 371.…”
Section: Introductionsupporting
confidence: 81%
“…In order to detect weak fluctuations we have performed aperture photometry by intergrading counts within a circular aperture of 7.5 arcsec centered on the objects Standard stars from Landolt (1992) were observed during the nights of 5, 6 October 2001 and calibration of 5field stars close to the objects (and subsequently of the sources) to the standard system was made, using DAOPHOT. The calibrated magnitudes of the sources were corrected for galactic reddening using the values of A B =0.269, A R =0.166 and A I =0.120 for PKS 2254+074 and A B =0.214, A R =0.133, A I =0.096 for S5 1803+784, converted into flux and corrected for the contribution of the host galaxy to the measured flux in each band as described in Xilouris et al (2006). The subtraction of the host galaxy contribution was not possible in the case of S5 1803+784 since it was unresolved in Pursimo et al (2002).…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…In newer optical observations (filters B, I), it was confirmed that 3C 371 has significant low-amplitude variability on a time scale from several hours to several days. Moreover, there is a strong correlation between the B and I bands on short and long time scales [24].…”
Section: Discussionmentioning
confidence: 99%